THE IMPACT OF AUTOMATION ON SERVICE WORKERS: A TECHNICAL ANALYSIS - Shradha Kohli (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This technical analysis examines the profound impact of automation technologies on service workers across various industries. It explores the key technological drivers of this transformation, including artificial intelligence, machine learning, robotic process automation, and the Internet of Things. The paper analyzes both the challenges and opportunities presented by automation, discussing job displacement, creation of new roles, productivity augmentation, and the emerging skill gap. Through case studies in banking and hospitality, it illustrates the real-world applications and effects of these technologies. The analysis also addresses ethical considerations, policy implications, and potential mitigation strategies to navigate the changing landscape of work in the service sector. By providing a comprehensive overview of the current state and future outlook of automation in services, this paper aims to inform policy-making, business strategies, and individual career decisions in an increasingly automated world.